External and internal architecture of nests of fungus-growing ants of the genera Cyphomyrmex, Mycetarotes, Mycocepurus, Myrmicocrypta, and Trachymyrmex (Hymenoptera: Formicidae) - Moreira, A. A.; Bueno, O. C. [UNESP]; Camargo, R. S. [UNESP]; Castellani, M. A.; Leite, S. A.; Zanuncio, J. C.; Sabattini, J. A.; Paula, R. C. A. L.; Lemos, R. N. S.; Coelho, B. S.; Oliveira, N. C. (FapUNIFESP (SciELO), 2025)
Studying the nest structures of fungus-growing ants of the genera Cyphomyrmex, Mycetarotes, Mycocepurus, Myrmicocrypta, and Trachymyrmex is essential to understanding their ecological role. Structural variations affect adaptation of these ants and their impact on agriculture and forest ecosystems. The internal and external structures of 49 fungus-growing ant nests were marked over three months, with four, seven, 31, four, and three nests, respectively, of the genera Cyphomyrmex, Mycetarotes, Mycocepurus, Myrmicocrypta, and Trachymyrmex (Hymenoptera: Formicidae: Attini) were described. The study were studied in the João Dias da Silveira Campus (Bela Vista) of the São Paulo State University (UNESP) in Rio Claro, São Paulo state, Brazil (22°23'73" S and 47°32'53" W). Forty-nine nests were marked over three months, with four, seven, 31, four, and three nests, respectively, of the genera Cyphomyrmex, Mycetarotes, Mycocepurus, Myrmicocrypta, and Trachymyrmex Four spherical chambers were observed in Cyphomyrmex nests, with height, width, length, and depth, respectively, of 2.8 cm, 2.5 cm, and 2.1 cm, and 15 cm to 30 cm. A single spherical chamber at a depth from 10 to 25 cm was observed in a Mycetarotes sp. nest and in each of the 31 nests of Mycocepurus sp. and Myrmicocrypta sp., with height, width, length, and depth, respectively, of 3.6 cm, 4.5 cm, and 4.1 cm, and 10 to 110 cm; and 5 cm, 5.9 cm, 6.3 cm, and 10 cm to 72 cm. The number of fungus chambers ranged from one to four per Trachymyrmex sp. nest, at depths between 15 cm and 205 cm and height, width, and length, respectively, of 3.9 cm, 7.2 cm, and 7.9 cm. Variations in the internal and external structures of Attini ant nests indicate that they should be considered to understand the ecology of these insects.